Penerapan Konsep Edutainment Dalam Pembelajaran Di Pendidikan Anak Usia Dini (PAUD) - Santoso Santoso (Universitas Muria Kudus, 2018)
Playing for early childhood is an activity or activity that has significance for the growth of the child, because playing directly gives influence to the child's growth and development. The learning approach to early childhood education in kindergarten as well as in family planning, TPA and SPS is more oriented towards learning approach through play. Edutaiment as a learning process designed by combining the educational content and entertainment in harmony, so that learning activities take place with fun. Fun, interesting, creative, and innovative learning is a concept of edutainment learning, as the basic concept of edutainment is an effort to make learning happen in a conducive, comfortable and fun atmosphere.